Multiple credit constraints and timevarying macroeconomic dynamics - Marcus Mølbak Ingholt (Norges Bank, 2020)
I explore the macroeconomic implications of borrowers facing both loan-to-value (LTV) and debt-service-to-income (DTI) limits, using an estimated DSGE model. I identify when each constraint dominated over the period 1984-2019: LTV constraints dominate in contractions, when house prices are relatively low - and DTI constraints dominate in expansions, when interest rates are relatively high. I also find that DTI standards were relaxed during the mid-2000s' boom, and that lower DTI limits or higher interest rates, but not lower LTV limits, would have prevented the boom. Finally, county panel data attest to multiple credit constraints as a source of nonlinear dynamics.
hdl:11250/2711211
Keywords: C33; D58; E32; E44; 330; Multiple credit constraints; Nonlinear estimation of DSGE models; State-dependent credit origination